TOPONIMI DESA DIKECAMATAN TILONGKABILA BERDASARKAN FAKTOR GEOGRAFI - Eraku, Sunarty Sully; Asnani, Asnani; Koem, Syahrizal (Jurnal Swarnabhumi : Jurnal Geografi dan Pembelajaran Geografi, 2023)
Tilongkabila is one of the districts in Bone Bolango regency. which consists of 14 villages. Every village possesses different toponyms and historical backgrounds, i.e., Berlian, Bongohulawa, Bongoime, Bonggopini, Butu, Iloheluma, Lonuo, Motilango, Moutong, Permata, Tamboo, Toto Utara, Tungulo, and south Tungulo village.Â  This research aimed to study toponym geography in TilongkabilaDistrict.It employed a qualitative descriptive method and spatial approach analysis. The data was collected through observation, interviews, documentation, and library research. The result showed two factors related to the basis of village toponymy in Tilongkabiladistrict. First, non-physical geographic factors (social and cultural aspects)were measured by 78%. Further, physical factors such as the embodiment aspect are influenced by 27%. All in all, the study concluded that non-physical geographic factors influenced the village toponymy in TilongkabilaDistrict.